2016
DOI: 10.18632/oncotarget.11043
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 confers resistance to gefitinib in lung adenocarcinoma via a MET/AKT-dependent positive feedback loop

Abstract: Gefitinib resistance remains a major problem in the treatment of lung adenocarcinoma. However, the molecular mechanisms of gefitinib resistance are not fully understood. In this study, we characterized the critical role of transcription factor Forkhead box protein M1 (FOXM1) in gefitinib resistance of lung adenocarcinoma cells. In vitro drug sensitivity assays demonstrated that FOXM1 inhibition sensitized PC9/GR and HCC827/GR cells to gefitinib, whereas FOXM1 overexpression enhanced PC9 and HCC827 cell resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The latter has been repeatedly implicated in drug-resistant solid cancers; e.g., in retinoblastoma [ 35 ], bladder cancer [ 36 ] and colorectal cancer [ 37 ], in which the heightened drug-efflux activity could be functionally linked to FOXM1-dependent upregulation of ABCC4, ABCG2 and ABCC10, respectively. Also playing a role may be other pathways of drug resistance that operate in solid tumors [ 38 ]; e.g., inhibition of ubiquitination-dependent FOXM1 degradation via interacting proteins, such as OTUB1 (OTU deubiquitinase, ubiquitin aldehyde binding 1) [ 39 ]; crosstalk of FOXM1 with other cellular signal transduction pathways, such as HGF / Met (hepatocyte growth factor / Met proto-oncogene, receptor tyrosine kinase) [ 40 ] and AKT (AKT serine / threonine kinase 1) [ 41 ]; and metabolic changes that effect increased oxidative defense capacity, as seen in radio-resistant head and neck squamous cell carcinoma [ 42 ]. Targeting the interactions and pathways described above – perhaps in conjunction with targeting FOXM1 directly using established [ 43 ] or emerging [ 44 ] small-drug inhibitors – may afford the re-sensitization of relapsed FOXM1 High myeloma to Bz and other drugs that were effective at earlier stages of myeloma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been repeatedly implicated in drug-resistant solid cancers; e.g., in retinoblastoma [ 35 ], bladder cancer [ 36 ] and colorectal cancer [ 37 ], in which the heightened drug-efflux activity could be functionally linked to FOXM1-dependent upregulation of ABCC4, ABCG2 and ABCC10, respectively. Also playing a role may be other pathways of drug resistance that operate in solid tumors [ 38 ]; e.g., inhibition of ubiquitination-dependent FOXM1 degradation via interacting proteins, such as OTUB1 (OTU deubiquitinase, ubiquitin aldehyde binding 1) [ 39 ]; crosstalk of FOXM1 with other cellular signal transduction pathways, such as HGF / Met (hepatocyte growth factor / Met proto-oncogene, receptor tyrosine kinase) [ 40 ] and AKT (AKT serine / threonine kinase 1) [ 41 ]; and metabolic changes that effect increased oxidative defense capacity, as seen in radio-resistant head and neck squamous cell carcinoma [ 42 ]. Targeting the interactions and pathways described above – perhaps in conjunction with targeting FOXM1 directly using established [ 43 ] or emerging [ 44 ] small-drug inhibitors – may afford the re-sensitization of relapsed FOXM1 High myeloma to Bz and other drugs that were effective at earlier stages of myeloma therapy.…”
Section: Discussionmentioning
confidence: 99%
“…FoxM1 is a member of the Forkhead box (Fox) transcription factor family, which has been shown to be over-expressed in various cancers and studies have shown that alterations in FoxM1 signaling were associated with carcinogenesis. FoxM1 is substantially elevated in several aggressive human carcinomas and can contribute to oncogenesis in many tissue types, including breast [ 12 ], hepatocellular [ 13 ], prostate [ 14 ], lung [ 15 ], and colorectal cancers [ 16 ]. Aberrant FoxM1expression was found to be a common molecular alteration in malignant glioma [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…(5,28) Our previous microarray data and various other studies indicated that both EGFR and MET can regulate FOXM1 expression. (6,(23)(24)(25)(26)(27) Here we report that TCPOBOP-driven FOXM1 induction and its downstream gene network activation was remarkably impaired in [MET KO + EGFRi] mice, which might contribute to attenuated proliferation in our model. Conversely, the inverse phenotype to our model (i.e., increased proliferation but reduced expression of drug metabolic enzymes) previously reported in β-catenin KO mice following TCPOBOP treatment was attributed to increased FOXM1 levels.…”
Section: Discussionmentioning
confidence: 77%
“…Our previous data and several other reports indicated that both MET and EGFR can regulate an important transcription factor, FOXM1, which governs transcription of genes important for DNA replication and mitosis. (6,(23)(24)(25)(26)(27) FOXM1 is considered to be critical for inducing TCPOBOP-mediated hepatocyte proliferation. (3,5,14,16,22,28) Consistent with these previous reports, FOXM1 was remarkably induced by TCPOBOP at all of the time points in control mice with peak induction (10-fold) coinciding with the time point of peak proliferation (day 2) ( Fig.…”
Section: Downregulation Of Foxm1 Transcription Factor and Its Downstrmentioning
confidence: 99%